Congenital anterior urethrocutaneous fistula revisited - Agarwal, Pawan (Indian Journal of Plastic Surgery, 2004)
Congenital anterior urethrocutaneous fistulas are rare. A case of this unusual anomaly is presented with review of literature, discussion of the possible etiology and management strategy.
Keywords: Congenital; fistula; urethrocutaneous